Safety and health before and after Marikana: subcontracting, illegal mining and trade union rivalry in the South African mining industry. Issue 163 (2nd January 2020) - Stewart, Paul; Bezuidenhout, Andries; Bischoff, Christine
ABSTRACT: Mine and worker Occupational Health and Safety (OHS) remains crucial given the historically dismal record of fatalities and accidents in mining in South Africa. OHS also played a central role in the resurgence of trade unionism of black South African mineworkers in the 1980s. While the OHS literature has the workplace as its predominant focus, this article explores three factors relating to conditions external to and beyond mining production: subcontracting, illegal mining and inter-union rivalry. By drawing on empirical studies conducted over two decades, employing a range of research methodologies, the article shows how these factors impact negatively on the mechanisms regulating safety and occupational health. The article concludes that understanding the OHS environment cannot remain restricted to the underground mining workplace. Instead, it points to a broader conceptualisation of OHS and notes the implications for worker politics and progressive research practice.